2013
DOI: 10.1088/1367-2630/15/12/125008
|View full text |Cite
|
Sign up to set email alerts
|

Observation of energetic protons trapped in laboratory magnetic-tower jets

Abstract: Preliminary results of the self-emission of charged particles from magnetically driven plasma jets has been investigated. The jets were launched and driven by a toroidal magnetic field generated by introducing a ∼1.4 MA, 250 ns electrical current pulse from the MAGPIE generator into a radial wire array. This configuration has shown to reproduce some aspects of the astrophysical magnetic-tower jet launching model, in which a jet is collimated by a toroidal magnetic field inside a magnetic cavity. The emission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…There is a significant experimental effort to study the MHD stability of plasma jets in the laboratory in conditions relevant for astrophysical environments 11,[16][17][18][19][20][21] . However, laboratory-produced plasma jets are generally far more collisional than those naturally occurring in space or astrophysical settings.…”
Section: Role Of Coulomb Collisions On Ion Acceleration Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…There is a significant experimental effort to study the MHD stability of plasma jets in the laboratory in conditions relevant for astrophysical environments 11,[16][17][18][19][20][21] . However, laboratory-produced plasma jets are generally far more collisional than those naturally occurring in space or astrophysical settings.…”
Section: Role Of Coulomb Collisions On Ion Acceleration Efficiencymentioning
confidence: 99%
“…These include the flaring activity and energetic particle generation in jets emanating from the solar atmosphere [2][3][4] , the synchrotron emission from bright knots and cosmic ray acceleration in jets from active galaxies [5][6][7] , among others. These instabilities are also associated with violent disruptions and particle acceleration in laboratory fusion devices, such as Tokamaks 8 and Z-pinches [9][10][11] . Yet, the detailed physics underlying how the development of such instabilities in jets accelerates particles remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A progress in increasing the number of fast deuterons for the neutron production in Z -pinches has been reported by Klir et al [86]. Interestingly, the generation of fast particles was also observed in laboratory astrophysics experiments [91], where protons with energies significantly exceeding the applied voltage were detected in the geometry of magnetic tower jets.…”
Section: Energetic Particles and Beamsmentioning
confidence: 80%
“…It is shown that these processes are important candidates to generate magnetic fields in the presence of strong velocity shears, which may naturally originate in energetic matter outbursts of active galactic nuclei and gamma-ray bursters. Suzuki-Vidal et al (2013) show preliminary results of the self-emission of charged particles from magnetically driven plasma jets has been investigated. This configuration has shown to reproduce some aspects of the astrophysical magnetic-tower jet launching model (e.g.…”
mentioning
confidence: 99%